ENTREPRENEURSHIP EDUCATION ASSISTANCE BASED ON LOCAL WISDOM TO INCREASE BUSINESS INTEREST AMONG HIGH SCHOOL STUDENTS - Samsudin, Samsudin (Journal of Community Engagement in Economics, 2024)
The importance of entrepreneurship education has grown significantly as it prepares students to adapt to economic changes, create job opportunities, and contribute to local economies. However, many high school students lack sufficient exposure to practical business knowledge, particularly in regions where access to formal entrepreneurship education is limited. By integrating local wisdom into entrepreneurship education, students can gain valuable insights that not only enhance their business skills but also strengthen their understanding of their cultural heritage. Local wisdom, rooted in community traditions and practices, offers a unique perspective on sustainable and resource-efficient business practices. This approach can provide students with a sense of identity and pride, motivating them to become active participants in the local economy. Incorporating local wisdom into entrepreneurship education is especially relevant for high school students as it can encourage them to explore business opportunities within their communities. This model promotes respect for cultural values while fostering innovation in a familiar context. The guidance provided through this approach can increase students' interest in business by making entrepreneurship more relatable and achievable. Furthermore, this model addresses the gap between theoretical education and real-world applications, preparing students to apply entrepreneurial skills that are in harmony with local values and resources. This research seeks to explore the effectiveness of entrepreneurship education based on local wisdom in enhancing students' interest in pursuing business ventures. Through targeted assistance and culturally relevant content, this program aims to equip students with the necessary skills and motivation to become future entrepreneurs who contribute positively to their communities.